A Systematic Literature Review: Project-Based Learning to Empower Students' Science Process Skills - Firdausi, Nurul; Sugiharto, Bowo; Karyanto, Puguh (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
Science process skills are an essential aspect that supports critical, creative, collaborative, and communicative thinking skills. The reality reveals that science learning in schools is still dominated by traditional methods focusing on memorising concepts. Project-Based Learning (PjBL) offers a promising approach to improving KPS. PjBL is a student-centred learning model, where students work collaboratively to design, implement, and evaluate projects that are relevant to real life. This study determines the effect of the project-based learning model on empowering students' science process skills by using a systematic literature review (SLR). Systematic Literature Review involves searching and analysing relevant literature from various sources published from 2016 to 2024. A systematic method could identify relevant literature studies to the pre-determined criteria. The applied content analysis ensured the model, method, focus, and results achieved from the study. The results indicate that (a) project-based learning improves students' science process skills, (b) project-based learning is feasible to use for teaching and learning activities, and (c) project-based learning is effective in science learning, especially for improving science process skills. Educators are advised to consider using the project-based learning model in learning strategies to support students' science skills development comprehensively.